The crystal of eternity and the matter of events: The Christian message in Flannery O’Connor’s works - Głąb, Anna (Litteraria Copernicana, 2025)
This article discusses the Christian message present in Flannery O’Connor’s fiction. The author begins by exploring the main ideas in O’Connor’s essays included in the volume Mystery and Manners, and thus outlines the context of her literary work. First, the author situates the American writer’s fiction within the context of her era, which was characterized by both unbelief and the search for God. The author aims to answer the question of how O’Connor conveys the human experience of encountering God in a way that is both natural and supernatural, without resorting to simplification or sentimentalism. This introduction serves as a basis for an analysis of O’Connor’s artistic vision, which focuses on the issue of human salvation. The author employs literary and philosophical categories identified in O’Connor’s texts. These include the mystery and texture of events, the habitus of art, and anagogical reading. The author also explores the significance of the grotesque and humor in O’Connor’s Christian message. She discusses the short story “A Good Man Is Hard to Find” as an example of how the novelist conveys the Christian message in her fiction.